If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + -3 + 6x = -10 Reorder the terms: -3 + x + 6x = -10 Combine like terms: x + 6x = 7x -3 + 7x = -10 Solving -3 + 7x = -10 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + 7x = -10 + 3 Combine like terms: -3 + 3 = 0 0 + 7x = -10 + 3 7x = -10 + 3 Combine like terms: -10 + 3 = -7 7x = -7 Divide each side by '7'. x = -1 Simplifying x = -1
| 4+3(4n+3)-n= | | 5k-1/2=3/2 | | 6s-2=8s | | 5(x-8)=3(3x-40) | | 4+3(4n+6)-n= | | 9x-6(x-1)=1 | | 6(d-6)=4(d-60)+2d | | -7x+(-7x-30)=36 | | 9mn/4n | | -2x^2+6x+8=12 | | -1=-5-4s | | 18z^3+9z^2-50z-25=0 | | x^2=y^2-20.25 | | 4(-5x+35)-x+7=0 | | 5x/2-8=2x-7/6 | | 2s+7=-5s | | 10a-83=203 | | X=(18+8) | | x=(x)(x) | | 34-2x=80 | | X^2-76+1380=0 | | 258=175-w | | 250=10e | | -2(2q-4)=10q-20 | | 11y+12=45 | | Sin(x)=-0.62 | | 9-7p=8 | | 09-7p=8 | | x+18+3*x=74 | | 8w+2=90 | | 11/h-5=7/5-h | | 68x=y-2875 |